O valor probante e a dimensão do inquérito civil nas ações civis públicas ajuizadas pelo Ministério Público em questões ambientais - Faria, Alessandra Maria de Almeida (2016)
The aim of this work is the study of the probative value and the size of the civil investigation in civil class actions filed by public ministry in environmental issues. Initially, because it is an instrument sporting character of officialdom, exclusive of the public ministry, and the specificity that environmental issues have, it sought to prove that the evidence within it need not be judicialized, and thus there would be greater efficiency in environmental protection. Meanwhile, not confirmed the hypothesis proposed at the beginning of this study, therefore, even if the observation of the adversarial principle and the full defense is necessary, because it is an administrative procedure and because of the principle of legal certainty. For last, one can not forget the size of the civil investigation on environmental issues has, as its use in deferred contradictory to the principle of effectiveness of the investigative procedure, the reversal of the burden of proof and the commitment to conduct adjustment.